1996
DOI: 10.1063/1.115913
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the confinement potential of a quasi-one-dimensional electron gas by lateral p-n junctions

Abstract: Articles you may be interested inFarinfrared study of a quasionedimensional electron gas formed on (100)GaAs facets with hole gas sidegates on a (311)A GaAs substrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Limited success can be achieved through a combination of epitaxial growth followed by a growth interrupt for surface modification e.g., ex situ mesa etch or high-energy ion implantation before a subsequent regrowth stage. 1,2 The technique of shadow masking may also be employed for the formation of laterally graded doped structures. 3 These methods, though proven viable, possess numerous inherent drawbacks ranging from a lack of flexibility to low yield ͑''one off success''͒.…”
Section: Introductionmentioning
confidence: 99%
“…Limited success can be achieved through a combination of epitaxial growth followed by a growth interrupt for surface modification e.g., ex situ mesa etch or high-energy ion implantation before a subsequent regrowth stage. 1,2 The technique of shadow masking may also be employed for the formation of laterally graded doped structures. 3 These methods, though proven viable, possess numerous inherent drawbacks ranging from a lack of flexibility to low yield ͑''one off success''͒.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This improvement in the performance of the resonant tunneling device, by hydrogen radical cleaning of the patterned substrate surface, has been achieved at a cleaning temperature of only 466°C. These results indicate that not only is hydrogen radical cleaning effective at contaminant removal but results in a cleaned surface suitable for regrowth of sensitive device structures.…”
mentioning
confidence: 99%
“…Further details related to device fabrication may be found in Ref. 8. After wedging the substrate to avoid interference effects in FIR CR transmission measurements, the angular dependence of Shubnikov deHaas ͑SdH͒ oscillations suggested that the plane of the electron gas made an angle of 19͑Ϯ1͒°with the wedged substrate.…”
mentioning
confidence: 99%